Angina bullosa hemorrhagica of the oral cavity in a COVID-19–positive patient: a rare case report - Shrestha, Roshani; Rajbhandari, Pradeep (International Journal of Scientific Reports, 2026)
Angina bullosa hemorrhagica (ABH) is a benign condition characterized by the sudden onset of painless, blood-filled bullae in the oral mucosa without systemic or hematologic disorders. During the COVID-19 pandemic, both virus-induced coagulopathy and anticoagulant therapy may be etiologies of unusual bleeding manifestations. A 46-year-old male presented with a sudden, painless swelling on the inner cheek that gradually enlarged over three days. The patient had a recent history of severe COVID-19 infection, treated with paracetamol, corticosteroids, and anticoagulants around two weeks before this lesion. Intraoral examination revealed a well-defined bluish-purple lesion on the right buccal mucosa, measuring approximately 3 cm, with no signs of trauma, ulceration, or active bleeding. Hematologic investigations showed normal hemoglobin and platelet counts, mildly prolonged PT and aPTT, slightly elevated INR, and increased D-dimer levels. The lesion was managed conservatively and resolved spontaneously within a week. This case highlights the potential for anticoagulant-associated or post-COVID microvascular fragility leading to oral mucosal hematomas such as ABH. Clinicians should remain vigilant about spontaneous oral hemorrhagic lesions in COVID-19 patients receiving anticoagulant therapy.